A violação dos direitos territoriais dos povos indígenas a partir do novo marco regulatório da mineração - Varão, Lorena Lima Moura (2018)
In Brazil, there are constant attacks to human rights masked under the pretext of development, improvement of life quality and increase in the number of jobs. In this sense, the research focuses on the process of resistance organized by indigenous peoples in opposition to the extraction of mineral resources by large mining enterprises, notably in relation to the violation of these peoples’ territorial rights. Given this point, the following problem arises: to what extent does the new mining regulatory framework allow mining companies to violate the territorial rights of indigenous peoples in Brazil? We work with the hypothesis that the new regulatory framework of the mining sector is based on the classic concept of private property, and therefore does not recognize the collective right of indigenous peoples to their traditional territory. The overall objective is to analyze whether there is a possibility of regulating mining without damaging the human rights of such peoples. Specifically, it aims to characterize mining activity within the neo-extractive context implemented in Brazil, to point out the opposition between mining regulations based on the collective rights of those peoples, and to analyze how the law legitimizes the violations committed by mining companies in disregard of the territorial rights of indigenous peoples. The methodological approach used to achieve the objectives, detect errors and assist decision making was the inductive one. As for the research technique, this work combines documentary with bibliographic methods.